Adenoma de células basais no Instituto Nacional de Câncer: experiência recente com 30 casos - Cordeiro, Mirna Scalon (2010)
Basal cell adenoma (BCA) is an epithelial benign tumor of the salivary glands of unusual occurrence. It has been usually reported as a slow-growing and asymptomatic lesion, occurring mainly in the parotid of adults or elder, more frequently in females. The present study aimed to report the recent experience with this disease in a Brazilian Government Center of reference for research and treatment of neoplasms, the National Institute of Cancer, describing the clinical-demographic features of 30 BCA identified from 1996 to 2006, which corresponds to 2,7% of all salivary glands at the same period. Females were prevalent, as well as elder patients and lesions in the parotid glands. Harmful habits were not frequent. An interesting finding was the high frequency of symptomatic tumors. Fine-needle aspiration biopsy was the main diagnostic procedure, and it was accurate to driven the treatment. Most of the lesions were treated by superficial parotidectomy and no recurrences were observed. The present study ratifies the indolent biological behavior of basal cell adenomas, while the high frequency of symptoms deserves further investigation.